Visualization of material interface stability - Obermaier, H.; Fang Chen; Hagen, H.; Joy, K. I. (2012 IEEE Pacific Visualization Symposium, 2012)
Material interfaces and free surfaces are a topic of increasing interest in the field of computational fluid dynamics. In parts, reconstructed interfaces from such multi-fluid simulations behave like classic integral surfaces as known in the visualization community, while other regions of the surface undergo topological changes or behave orthogonally to what is expected by the underlying flow field. Thus, the analysis of the flow field in connection with material interface shape and topology is a challenging task. We develop a technique that facilitates visualization and analysis of such complex material interface behavior over time. For this matter, we track a surface parametrization of time-varying material interfaces and identify locations of interaction between material interfaces and fluid particles. Splatting and surface visualization techniques produce an intuitive representation of the derived interface stability. Our results demonstrate, how the interaction of the flow field with the material interface can be highlighted by appropriate extraction and visualization techniques and how the developed techniques can aid analysis of mixing and material interface consistency.